Kestävä kehitys ja aineenopettajaksi opiskelevien pedagogiset opinnot Subject student teachers’ perceptions of sustainable development in the pedagogical studies - Eija Yli-Panula; Irmeli Palmberg; Eila Jeronen (Suomen ainedidaktinen tutkimusseura, 2022)
The aim of this research was to study student teachers’ perceptions of their competence concerning sustainable development (the coverage and usefulness of SD in their pedagogical studies) and of their opportunities to influence pupils’ way of taking responsibility of the environment. The data were collected using a questionnaire and interviews. The results show that the student teachers regarded the teaching of SD as being important and useful. Themes such as solving conflicts related to environmental problems, discussion of the practical solutions of environmental problems and processing the themes concerning social sustainability were seen as the central ones by the student teachers. They were familiar with the obligatory contents of SD in the national core curricula. They also regarded the contents of SD as subject bound, future oriented and including personal meanings. However, the student teachers lack a holistic understanding of SD and of its teaching at school. SD should be included in the pedagogical study program due to the shortage and incoherence of SD studies. Results show that content-based and pedagogical SD studies as presented in the national core curricula should also be included in the compulsory studies for all Finnish subject student teachers.
Jatkuvuus ja muutos opettajankoulutuksessa